How far can forecasting models forecast? Forecast content horizons for some important macroeconomic variables - John W. Galbraith; Greg Tkacz (Bank of Canada, 2007)
For stationary transformations of variables, there exists a maximum horizon beyond which forecasts can provide no more information about the variable than is present in the unconditional mean. Meteorological forecasts, typically excepting only experimental or exploratory situations, are not reported beyond this horizon; by contrast, little generally accepted information about such maximum horizons is available for economic variables. The authors estimate such content horizons for a variety of economic variables, and compare these with the maximum horizons that they observe reported in a large sample of empirical economic forecasting studies. The authors find that many published studies provide forecasts exceeding, often by substantial margins, their estimates of the content horizon for the particular variable and frequency. The authors suggest some simple reporting practices for forecasts that could potentially bring greater transparency to the process of making and interpreting economic forecasts.
Keywords: C53; 330; Econometric and statistical methods; Business fluctuations and cycles; Konjunkturforschung; Wirtschaftsprognose; Zeit; Statistische Methode